Effects of Virtual Exercise Rehabilitation In-Home Therapy Compared with Traditional Care After Total Knee Arthroplasty: VERITAS, a Randomized Controlled Trial. (15th January 2020) - Prvu Bettger, Janet; Green, Cynthia L.; Holmes, DaJuanicia N.; Chokshi, Anang; Mather, Richard C.; Hoch, Bryan T.; de Leon, Arthur J.; Aluisio, Frank; Seyler, Thorsten M.; Del Gaizo, Daniel J.; Chiavetta, John; Webb, Laura; et al.
Abstract : Background: Financial burden for patients, providers, and payers can reduce access to physical therapy (PT) after total knee arthroplasty (TKA). The purpose of the present study was to examine the effect of a virtual PT program on health-care costs and clinical outcomes as compared with traditional care after TKA. Methods: At least 10 days before unilateral TKA, patients from 4 clinical sites were enrolled and randomized 1:1 to the virtual PT program (involving an avatar [digitally simulated] coach, in-home 3-dimensional biometrics, and telerehabilitation with remote clinician oversight by a physical therapist) or to traditional PT care in the home or outpatient clinic. The primary outcome was total health-care costs for the 12-week post-hospital period. Secondary (noninferiority) outcomes included 6 and 12-week Knee injury and Osteoarthritis Outcome Score (KOOS); 6-week knee extension, knee flexion, and gait speed; and 12-week safety measures (patient-reported falls, pain, and hospital readmissions). All outcomes were analyzed on a modified intent-to-treat basis. Results: Of 306 patients (mean age, 65 years; 62.5% women) who were randomized from November 2016 to November 2017, 290 had TKA and 287 (including 143 in the virtual PT group and 144 in the usual care group) completed the trial. Virtual PT had lower costs at 12 weeks after discharge than usual care (median, $1, 050 compared with $2, 805; p < 0.001). Mean costs were $2, 745 lower for virtual PT patients. Virtual PT patients had fewer rehospitalizations than the usual care group (12 compared with 30; p = 0.007). Virtual PT was noninferior to usual PT in terms of the KOOS at 6 weeks (difference, 0.77; 90% confidence interval [CI], −1.68 to 3.23) and 12 weeks (difference, −2.33; 90% CI, −4.98 to 0.31). Virtual PT was also noninferior to usual care at 6 weeks in terms of knee extension, knee flexion, and gait speed and at 12 weeks in terms of pain and hospital readmissions. Falls were reported by 19.4% of virtual PT patients and 14.6% of usual care patients (difference, 4.83%; 90% CI, −2.60 to 12.25). Conclusions: Relative to traditional home or clinic PT, virtual PT with telerehabilitation for skilled clinical oversight significantly lowered 3-month health-care costs after TKA while providing similar effectiveness. These findings have important implications for patients, health systems, and payers. Virtual PT with clinical oversight should be considered for patients managed with TKA. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.